Pemetaan Kesesuaian Lahan Tanaman Pangan pada Lahan Sawah Berbasis Sistem Informasi Geografis di Kecamatan Kuta Utara - Sinaga, Hany Dwi Gloria; Trigunasih, Ni Made; Arthagama, I Dewa Made; Mega, I Made; Narka, I Wayan; Soniari, Ni Nengah (Agrotrop : Journal on Agriculture Science, 2025)
Land Suitability Mapping for Food Crops in Paddy Fields based a Geographic Information System in North Kuta District.  The agricultural land that should be utilized to produce food has been converted into residential or non-agricultural land use. The results of the land evaluation can be adjusted to the carrying capacity and the land potential. This research aims to determine the suitability of actual and potential land for food crops, limiting factors, business improvements, and directions for appropriate land use in North Kuta District. The methods used in this research are survey, interview methods, and matching land quality/characteristics with plant growth requirements. Food crops evaluated include rice, corn, soybeans, and peanuts. The actual land suitability results at the research location for all food crops are classified as S3 (marginally suitable) and potentially classified as S1 (very suitable) to S2 (quite suitable) with texture limiting factors. Limiting factors that become obstacles in developing food crops in North Kuta District include rainfall, N-total, and P 2 O 5 . Improvements that can be made to increase land productivity at this research location are by adjusting crop patterns according to the season for the limiting factor of rainfall, applying urea or ZA fertilizer for the total N limiting factor, and fertilizing with TSP or SP-36 for the P 2 O 5 limiting factor. Directions for land use and priority crop commodities include rice, corn and soybeans in Tibubeneng Village, Kerobokan Village and Kerobokan Kelod Village, Canggu Village, Kerobokan Kaja Village and Dalung Village  as well as for peanuts is found in Kerobokan Kaja Village and Dalung Village.